ERP compatibility on business performance through the inventory system and internal integration. Issue 1 (January 2021) - Sebayang, P; Tarigan, Z J H; Panjaitan, T W S
Abstract: The information technology used by companies today is ERP (Enterprise Resources Planning) technology. This study aims to examine the role of ERP compatibility in improving the performance of MM-2100 manufacturing companies. Data is collected at manufacturing companies that have made ERP system adjustments. Data collection was carried out through questionnaires distributed to manufacturing companies, and as many as 78 questionnaires were obtained, which could be further processed. Retrieval of data using questionnaires submitted to the relevant section that has access to company inventory data. Data analysis was performed using the SEM-PLS technique using smart PLS software version 2.0. The results of the study show that ERP compatibility can increase internal information integration and inventory system continuously. However, ERP compatibility has no direct effect on manufacturing performance. Internal integration affects inventory systems and manufacturing performance with coefficients of 0.346 and 0.378, respectively. Internal integration allows other functions to be able to access inventory in the company. The company's inventory system that is controlled can perform efficiency and effectiveness for the company so that it has an impact on manufacturing performance with a coefficient of 0.766.